A dual-plate ITO-ITO generator-collector microtrench sensor: surface activation, spatial separation and suppression of irreversible oxygen and ascorbate interference. - Hasnat, M; Gross, A; Dale, SE; Barnes, E; Compton, R; Marken, F (2014)
Generator-collector electrode systems are based on two independent working electrodes with overlapping diffusion fields where chemically reversible redox processes (oxidation and reduction) are coupled to give amplified current signals. A generator-collector trench electrode system prepared from two tin-doped indium oxide (ITO) electrodes placed vis-à-vis with a 22 μm inter-electrode gap is employed here as a sensor in aqueous media. The reversible 2-electron anthraquinone-2-sulfonate redox system is demonstrated to give well-defined collector responses even in the presence of oxygen due to the irreversible nature of the oxygen reduction. For the oxidation of dopamine on ITO, novel "Piranha-activation" effects are observed and chemically reversible generator-collector feedback conditions are achieved at pH 7, by selecting a more negative collector potential, again eliminating possible oxygen interference. Finally, dopamine oxidation in the presence of ascorbate is demonstrated with the irreversible oxidation of ascorbate at the "mouth" of the trench electrode and chemically reversible oxidation of dopamine in the trench "interior". This spatial separation of chemically reversible and irreversible processes within and outside the trench is discussed as a potential in situ microscale sensing and separation tool.